2021
DOI: 10.1101/2021.11.23.21266755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome sequencing in the Parkinson’s disease clinic

Abstract: Background and ObjectivesGenetic variants impact both Parkinson’s disease (PD) risk and manifestations. While genetic information is of potential interest to patients and clinicians, genetic testing is rarely performed during routine PD clinical care. The goal of this study was to perform genome sequencing and examine patient interest in comprehensive genetic testing for PD in 2 academic movement disorder clinics.MethodsIn 208 subjects with PD (age=63 years, 67% male), genome sequencing was performed and filte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In a Central Asian study of an early-onset Parkinson's disease population in Kazakhstan, pathogenic mutations were found in only 6% of cases and only in the LRRK2 and PRKN genes, confirming regional differences between populations [46]. Another study on a heterogeneous population of 203 patients and all types of presentation showed a high yield of pathological variants of 20.19%, mainly in the GBA (10%) and LRRK2 (3%) genes [47]. Slightly lower but significant percentages were found in American patients of European origin, where the percentage of GBA variants was 7.1%, and SNCA, LRRK2, and PRKN variants were 2% [48].…”
Section: Discussionmentioning
confidence: 90%
“…In a Central Asian study of an early-onset Parkinson's disease population in Kazakhstan, pathogenic mutations were found in only 6% of cases and only in the LRRK2 and PRKN genes, confirming regional differences between populations [46]. Another study on a heterogeneous population of 203 patients and all types of presentation showed a high yield of pathological variants of 20.19%, mainly in the GBA (10%) and LRRK2 (3%) genes [47]. Slightly lower but significant percentages were found in American patients of European origin, where the percentage of GBA variants was 7.1%, and SNCA, LRRK2, and PRKN variants were 2% [48].…”
Section: Discussionmentioning
confidence: 90%